Cyclocarya paliurus triterpenoids attenuate glomerular endothelial injury in the diabetic rats via ROCK pathway. (12th June 2022) - Yang, Ru; Xu, Susu; Zhang, Xuanxuan; Zheng, Xian; Liu, Yao; Jiang, Cuihua; Liu, Jianjing; Shang, Xulan; Fang, Shengzuo; Zhang, Jian; Yin, Zhiqi; Pan, Ke
Abstract: Ethnopharmacological relevance: Cyclocarya paliurus (Batal.) Iljinskaja. ( C. paliurus ) is a distinctive traditional Chinese herb, with remarkable hypoglycemic capacity. Emerging evidence suggested that glomerular endothelial injury is a crucial pathological process of diabetic kidney disease (DKD). Our previous research found that C. paliurus triterpenoids fraction (CPT) has ameliorative effects on DKD. However, whether C. paliurus could counteract the glomerular endothelial injury of DKD is still undefined. Aim of the study: We aimed to investigate the effects of CPT on glomerular endothelial function and explore its underlying mechanisms with in vivo and in vitro experiments. Materials and methods: The effects and possible mechanisms of CPT on glomerular endothelial injury in streptozotocin (STZ)-induced diabetic rats and H2 O2 -challenged primary rat glomerular endothelial cells were successively investigated. Results: In vivo, we found that CPT treatment obviously decreased the levels of blood glucose, microalbumin, BUN and mesangial expansion. Additionally, CPT could ameliorate renal endothelium function by reducing the content of VCAM-1 and ICAM-1, and blocking the loss of glycocalyx. In vitro, CPT could also alleviate H2 O2 -induced endothelial injury. Mechanistically, CPT remarkably increased the phosphorylation levels of Akt and eNOS, decreased the expression of ROCK and Arg2 in vivo and in vitro . Noticeably, the favorable effects mediated by CPT were abolished following ROCK overexpression with plasmid transfection. Conclusion: These findings suggested that CPT could be sufficient to protect against glomerular endothelial injury in DKD through regulating ROCK pathway. Graphical abstract: Image 1